The interaction between medical ethics, case law and the National Health Insurance : a discussion of the South African health care crisis - Carstens, Pieter Albert, 1960- (University of Pretoria, 2026)
Dissertation (LLM (Medical law and ethics))--University of Pretoria, 2017.